Identifikasi Jenis Hama Tanaman Damar (Agathis alba) Di Hutan Lindung Sirimau Kota Ambon Provinsi Maluku - Cornelia M A Wattimena; Lily Pelupessy; SLA Selang (Faculty of Agriculture, Pattimura University, 2016)
Efforts to save the forest should be done to avoid forest damage by pests. This aim of this study was determine the type of pest and area of attack on the resin stand (Agathis alba) in conservation forest Sirimau, Maluku Province by used of survey method. The results of the study found that pests that destroy dammar in conservation forest Sirimau are leaf-eating pest (Valanga nigricormis) and stem borer (Massicus scapulatus). The damage caused by Valanga nigricormis at the seedling level was 92%, the weaning level was 72%, and the pole level was 64%. The damage caused by Massicus scapulatus at the tree level was 60%. The extent of attack of both types of pests was categorized as heavy to very heavy.